Pembangunan Ekonomi Masyarakat Melalui Agrowisata - Kader, Abdurrahman; Abd. Radjak, Darwin (Universitas Islam Malang, 2020)
This study is aims to examine the economic development of the Kalaodi community through agrotourism. In particular, this study is aims to examine the development of the agricultural potential of the Kalaodi village as an agro tourist attraction in Tidore City, and home industry development as an effort to improve the community's economy. This research use the desciptive qualitative approach, and the data analysis technique used is an interactive model, with stages: data condensation, display data, drawing/ verifiying. The results showed that the government of Tidore City did not yet have a Kalaodi agrotourism development program. However, the Kalaodi people have developed agriculture as an object of agrotourism. The business carried out by the community is utilizing the house yard as a family garden. In addition, the Kalaodi community has local wisdom in carrying out their profession as a farmer, namely farming that does not damage the forest and nature. This wisdom enriched the Kalaodi village agro tourism. The Kalaodi community also developed a home industry as a form of developing agrotourism in their village. Products of produced from the home industry are malinjo crackers and chips, souvenirs and jewelry and household furniture. Economically, the home industry business developed by the community has an impact on society such as helping the family economy.